Century of the exile: Colombia's displacement and land restitution in historical perspective, 1940s–1960s. Issue 3 (2nd September 2017) - Karl, Robert A.
ABSTRACT: The mid-twentieth-century Colombian conflicts known as La Violencia presented a crisis of displacement and property even more than one of mortality. This article considers the various land restitution initiatives undertaken during the early years of the National Front coalition (1958–1962), in particular the Conciliation and Equity Tribunals ( Tribunales de Conciliación y Equidad ) of 1960–1961. Reframing La Violencia around the issues of displacement and dispossession highlights the particular configuration of political violence and socio-economic relations in mid-century Colombia. By focusing on the Colombian state's efforts to remediate the effects of rural violence through the Tribunals and related institutions, the article introduces new perspectives on state–citizen relations in modern Colombia, including the relationship between legal institutions and attitudes toward the state. Colombia's experience with displacement and dispossession between the 1940s and 1960s also raises suggestive comparisons with ongoing Colombian government efforts to address the effects of rural violence.